Transformation project manager: an enabler of an enterprise resource planning (ERP) implementation success - John, Onyekachi Okugo (2013)
ERP business solution drives and improves business performance, meet business needs, support short and long term business strategic direction, but does not have the capability to make key business decisions on its own. ERP system provides data to assist people in orchestrating and making key business decisions that delivers increase return on investments. In ERP implementation project management, people (team, managements, and users) perspectives are the most challenging aspect to deal with. However, they are the most critical and important factor that determines whether ERP system implementation project will be a success or a failure. Transformational project manager set visions and goals, create new opportunities and values, and integrate and coordinate team diverse perspectives. He undertakes strategic and nonlinear thinking, and utilizes other people’s expertise, skills, and abilities, and develops new talents and human capital. In this research we used leadership behavioural characteristics and critical success factors of ERP implementation to develop the underlying transformational leadership core competence qualities of project manager, modelled leadership core competence of an ERP implementation project, and assessed how each of the leadership core competence quality relates to the ERP implementation success by using primary data obtained from respondents who participated as ERP implementation project team members. We believe that the leadership core competence qualities and the leadership core competence model will serve as ERP implementation toolkit, assists in the selection and development of training program for transformational project manager.